Carotid cavernous fistula (CCF) with coil embolization in interventional radiology: A case report - Eppy Buchori, MD; Hilman, MD; Muhamad Dony Ardiansyah, MD; Winarno Priyanto, MD; Prettyla Yollamanda, MD (Radiology Case Reports, 2023)
Carotid cavernous fistula (CCF) is a condition with abnormal flow from the carotid artery to the cavernous sinus. The characteristic clinical findings are ophthalmic monoplegia, ptosis, exophthalmos, chemosis, Horner's syndrome, facial pain, loss of sensation in the distribution of the trigeminal nerve, and headache. Digital subtraction angiography (DSA) is the gold standard modality for evaluating CCF. An 18-year-old patient came with decreased bilateral visual acuity after a traffic accident. CT angiography was performed on the patient and found a dilated right superior ophthalmic vein. CCF is present in the patient. The DSA procedure was performed on the patient, and embolization was performed on the right ophthalmic vein. On post-embolization angiography, the tubular structure is no longer visible, which is bilateral superior ophthalmic vein dilatation.